2022
DOI: 10.3892/etm.2022.11495
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and autoimmune predictive markers of response to anti‑PD‑1/PD‑L1 therapy in NSCLC and melanoma

Abstract: Immune checkpoint inhibitors (ICI) are a standard in cancer therapy, but few patients respond to the treatment. The aim of the present study was the determination of immunological markers for monitoring response to ICI. The present study included 74 patients receiving ICI in subsequent [group 1; non-small cell lung cancer (NSCLC)] and first-line setting (group 2; melanoma) and 30 patients with NSCLC receiving first-line chemotherapy. In groups 1 and 2 β-2 microglobulin (B2-MG), neopterin (NPT), IL-6, IL-18, HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Different levels of B2M have been shown to be prognostic factors for outcomes in various cancers [68] , [69] , [70] , [71] . Additionally, B2M has been found to correlate with ICI therapeutic response in NSCLC and melanoma [72] , [73] , likely due to its impact on tumor antigen presentation disruption [74] .…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of B2M have been shown to be prognostic factors for outcomes in various cancers [68] , [69] , [70] , [71] . Additionally, B2M has been found to correlate with ICI therapeutic response in NSCLC and melanoma [72] , [73] , likely due to its impact on tumor antigen presentation disruption [74] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, B2M has been shown to correlate with ICI therapeutic response in NSCLC and melanoma [65,66], likely through disruption of tumor antigen presentation [67].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of IL-18 is also associated with increased metastases in hepatocellular and breast carcinomas [162,163]. As for the role of IL-18 in predicting patients' response to immunotherapy, it was shown that patients with non-small cell lung cancer who respond to treatment had lower levels of IL-18 compared to non-responders [164], which contrasts with other studies in the same tumor type [140,141].…”
Section: Il-18: a Pro Tumoral Cytokinementioning
confidence: 90%